2024
DOI: 10.3390/ijms25084502
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Bioinformatics–Gene Network Approach Reveals Linkage between Estrogenic Endocrine Disruptors and Vascular Remodeling in Peripheral Arterial Disease

Vincent Avecilla,
Mayur Doke,
Madhumita Das
et al.

Abstract: Vascular diseases, including peripheral arterial disease (PAD), pulmonary arterial hypertension, and atherosclerosis, significantly impact global health due to their intricate relationship with vascular remodeling. This process, characterized by structural alterations in resistance vessels, is a hallmark of heightened vascular resistance seen in these disorders. The influence of environmental estrogenic endocrine disruptors (EEDs) on the vasculature suggests a potential exacerbation of these alterations. Our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…This has provided valuable insight into the complex molecular and mechanistic processes involved in CCM. Previously, it has been demonstrated that ID3 has interactions with various vascular/blood vessel diseases [5][6][7][8][9][10][11][12][13][14][15]22,23] however; this new information can help to build the foundation for additional research within the focus of gene expression networks, bioinformatics, and data analytics. The small sample size in the GEO study for our analysis of DEGs might restrict statistical power, which increases the risk of type II errors and bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has provided valuable insight into the complex molecular and mechanistic processes involved in CCM. Previously, it has been demonstrated that ID3 has interactions with various vascular/blood vessel diseases [5][6][7][8][9][10][11][12][13][14][15]22,23] however; this new information can help to build the foundation for additional research within the focus of gene expression networks, bioinformatics, and data analytics. The small sample size in the GEO study for our analysis of DEGs might restrict statistical power, which increases the risk of type II errors and bias.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitor of DNA Binding/Differentiation -3 (ID3), which is part of a group of genes (ID1, ID2, ID3, and ID4), has been known to be expressed in endothelial cells and important for endothelial cell activation and embryonic vasculogesis [5][6][7][8]. While known as a transcriptional regulator that prevents stem cell differentiation, ID3 has been identified to show overlapping functions such as gene knockout dependent on cellular context and can be activated from external environmental exposure [8][9][10][11][12][13][14][15][16]. While ID3 has been associated with vascular malformations such as Hereditary Hemorrhagic Telangiectasia [6,7], little is known about the association between ID3 and cerebral cavernous malformation.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen regulated gene transcription may modulate signaling to activate mTOR. Various studies have shown that estrogen and estrogen disruptors may promote various transcriptional regulators such as ID proteins to be involved in various molecular activities such as vascular remodeling, stem cell differentiation, and pulmonary dysfunction [3][4][5][6][7][8][9][10][11]. While genes such as TSC1 and TSC2 are known to be involved with LAM development [1][2][3][4][5], very little is known about other genes that are associated with the disorder.…”
Section: Introductionmentioning
confidence: 99%